If f(x) = 3x – 1 and g(x) = x + 2, find (f – g)(x). w O A. 4x+1 O B. 2x-3 o c. 2x-1 O D. 3 – 2x IR

Question

If f(x) = 3x – 1 and g(x) = x + 2, find (f – g)(x).
w
O A. 4x+1
O B. 2x-3
o c. 2x-1
O D. 3 – 2x
IR
SUBMI

in progress 0
Peyton 3 days 2021-10-11T15:21:37+00:00 1 Answer 0

Answers ( )

    0
    2021-10-11T15:22:43+00:00

    Known :

    f(x) = 3x – 1

    g(x) = x + 2

    Asked :

    (f – g)(x) = …?

    Answer :

    (f – g)(x)

    = (3x – 1) – (x + 2)

    = (3x – x) (-1 + 2)

    = 2x – 1

    So, (f – g)(x) equal to 2x 1 (C)

    Hope it helpful and useful :)

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )